Persepsi staf bukan akademik terhadap penampilan pelajar Universiti Malaysia Pahang - Hasmadi, Hassan; Jamal Rizal, Razali (Universiti Malaysia Pahang, 2019)
Student appearance in the style of dress at issue in the University Malaysia Pahang (UMP). The paper outlines a perception among non-academic staff to students, especially the appearance of the dress code. The study also focused on the factors that affect how students dress and the effects thereof. There are a total of 30 respondents among non-academic staff to answer questions UMP manually. The study found that peer influence, social media and follow the current fashion trends are the main factors that cause drastic changes in student clothing. In conclusion, the staff thought that the UMP students are easily influenced by outside elements where they are always dressed in a way according to their preferred style. This situation requires undergraduates need to make improvements.